A review of current knowledge and future trends in polymer/boehmite nanocomposites. (April 2022) - Kausar, Ayesha
Boehmite [bey-mahyt] is a unique aluminum oxide hydroxide nanostructure. It consists of nanosheets of octahedral aluminum ions with surface hydroxyl groups. Owing to exceptional reinforcing behavior, boehmite nanoparticles have gained immense attention as polymeric nanofillers. Essential matrices used with the boehmite based nanocomposites include poly(methyl methacrylate), polyethylene, polypropylene, polyamide, epoxy, and other polymers. In this review, all-inclusive considerations on the design, morphology, mechanical, thermal, electrical, ion conducting, flame retardancy, electrochemical, and other physical properties, and advances related to the polymer/boehmite nanocomposites are presented. The polymer/boehmite nanocomposites have been employed for the membranes (water filtration/dye removal), coatings (anti-corrosion/self-healing), Li-ion batteries, and non-flammability purposes.